My kind of wonderful [large type] - Shalvis, Jill (Shalvis, Jill. Cedar Ridge novel., 2016)
"Bailey Moore has an agenda: skiing in the Rockies, exploring castles in Europe, ballroom dancing in Argentina. With a second lease on life, she's determined not to miss a thing. Then item #1 comes with a six-foot-one ski god hot enough to melt a polar ice cap. Bailey doesn't want to miss out on him either, but Hudson Kincaid isn't the type of guy to love and let go. And as gorgeous as Cedar Ridge is, she's not planning to stick around. Now Hud will just have to convince Bailey to take a chance on her biggest adventure yet." -- Back cover.